First record of Galeodes indicus Pocock, 1900 (Arachnida: Solifugae: Galeodidae) from Rajasthan, India - Ruquaeya Bano; Sharmila Roy (Journal of Threatened Taxa, 2016)
During a regular survey to collect soil arthropods in Lasiurus sindicus Henrard grassland by pitfall methods at Chandan Village near Jaisalmer City, Rajasthan, we found a dead specimen of Galeodes indicus in a sample.  Galeodes indicus (Pocock, 1900) has been reported from Madhya Pradesh, Maharashtra, Andhra Pradesh and Telangana but so far was unknown to Rajasthan, India.  In this communication, we report Galeodes indicus from Jaisalmer District, Rajasthan, India.